2016
DOI: 10.1111/cns.12600
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin‐Related Protein 1 Promotes Mitochondrial Fission and Contributes to The Hippocampal Neuronal Cell Death Following Experimental Status Epilepticus

Abstract: Our findings suggest that activation of p-Drp1(Ser616) is related to seizure-induced neuronal damage. Modulation of p-Drp1(Ser616) expression is accompanied by decreases in mitochondrial fission, mitochondrial dysfunction, and oxidation, providing a neuroprotective effect against seizure-induced hippocampal neuronal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…In particular, chen et al. demonstrated that mitochondrial injury induced by oxidative and nitrative stress could trigger the caspase cascades via the release of cytochrome c, leading to cell apoptosis in hippocampus …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, chen et al. demonstrated that mitochondrial injury induced by oxidative and nitrative stress could trigger the caspase cascades via the release of cytochrome c, leading to cell apoptosis in hippocampus …”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study, 13 the viabilities of HT22 cells could significantly decrease when the cells were exposed to 40 μmol/L Aβ 25-35 for 24 hours. Thus, we selected 40 μmol/L as the optimal concentration of Aβ [25][26][27][28][29][30][31][32][33][34][35] for our subsequent research. HT22 cells were preconditioned with specified doses of NTP for 16 hours and subsequently treated with or without 40 μmol/L Aβ 25-35 for 24 hours.…”
Section: Cell Culture Differentiation Aβ 25-35 Preparation and Tmentioning
confidence: 99%
See 2 more Smart Citations
“…In a diabetic mouse model, GSK3β‐induced Drp1 phosphorylation at Ser‐616 involve in its synaptic deficits, and blockade of GSK3β by TDZD8 (an inhibitor of GSK3β) or inhibiting the fragmentation of mitochondria both tremendously improves mitochondrial and synaptic function. Mitogen‐activated protein kinase 1 (MAPK1) can cause over‐activation of Drp1 at Ser‐616 in HD knockin mouse‐derived striatal cells which were found by Roe et al causing mitochondria dysfunction finally leading to the occurrence of HD, and using U0126 (an inhibitor of MEK1/2) or Drp1 S616A (phosphorylation‐deficient mutant 1) canceled all of it (Chen et al, ; Chuang et al, ; Hyun, Min, & Kim, ; Jin et al, ; Kashatus et al, ; Xie et al, ).…”
Section: Posttranlational Modification Of Drp1 In Neural System Dysfumentioning
confidence: 99%